Intelligent packaging machine for fresh and live aquatic products - MA BENHE; WANG HAIHUA; CHEN CUIYUN; WANG MENGJIE; LI YANHUA (2021)
The invention discloses an intelligent packaging machine for fresh and live aquatic products. A device body is included, a conveying barrel is arranged in the device body, the lower middle portion of the conveying barrel is wrapped by a packaging film, conveying belts are arranged on the two sides of the middle of the bottom end of the conveying barrel, the conveying belts are tightly attached to the packaging film, and an air supply pipe and a water supply pipe are arranged in the conveying barrel; a sealing mechanism and a transverse heat sealing mechanism are arranged in front of the conveying barrel, the sealing mechanism comprises a first upper lifting plate and a first lower lifting plate, after a second air cylinder and a fifth air cylinder drive a sponge mat to make contact with the first lower lifting plate, an opening in the bottom end of the water supply pipe is located between the sponge mat and the first lower lifting plate or located behind the sponge mat, and an opening in the bottom end of the